After A Year of Follow Up Non-Cirrhotic Portal Hypertension Patient with Partial Spleen Embolization (PSE) Management - Akhmadu Muradi; Chyntia Olivia Maurine Jasirwan; Raden Suhartono; Patrianef Darwis; Dedy Pratama; Teguh Dwi Nugroho; Karina Zulkarnain (The Indonesian Society for Digestive Endoscopy, 2021)
Non-cirrhotic portal hypertension (NCPH) is a heterogeneous group of liver disorders leading to portal hypertension. There are multiple approaches to managing portal hypertension' clinical complications to treat/prevent spontaneous hemorrhage by mitigating thrombocytopenia. Portal hypertension complications have been traditionally managed with serial endoscopic variceal ligation (EVL) or with invasive open surgical procedures such as orthotopic liver transplantation (OLT) or portosystemic shunting, splenectomy.6–9 There are several risks associated with splenectomies, such as hemorrhagic complications or intraoperative blood loss.5,6,14 Partial Spleen Embolization (PSE) ‎may overcome the limitations of splenectomy and provide patients with an alternative treatment. An eighteen-year-old male has a splenomegaly history since he was 12 years old and has recurring hematemesis and melena. After performing abdominal computed tomography, laboratory studies, and several endoscopies, the results indicated secondary hypersplenism due to non-cirrhotic portal hypertension. The patient had 13 endoscopies and 2 EVL in 5 years. Despite adequate treatment, the patients developed recurrent variceal bleeding and no improvement in blood function. The patient underwent PSE at Integrated Cardiovascular Center in Dr. Cipto Mangunkusumo, General Hospital, Jakarta, Indonesia. It was performed through the femoral access with a PVA (polyvinyl alcohol) embolus. The procedure went successful, and there was no major complication with the patient. Twenty days after the patient had an abdominal CT scan, it showed no abscess, and the spleen volume was reduced by 20%. Long-term results over a year after the procedure are presented. PSE is a safe, effective, semi-invasive alternative to splenectomy in non-cirrhotic portal hypertension because it preserves functional spleen mass and avoids postprocedure accelerated liver disease or encephalopathy.